ANALISIS PERBANDINGAN PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA LAYANAN GPRS DI BANJARMASIN (STUDI PADA KARYAWAN DAN MAHASISWA POLITEKNIK NEGERI BANJARMASIN) - Norhafani . (INTEKNA informasi teknik dan niaga, 2013)
Phonecell customer has been growth in a large amount in last decade, so did the phone-cell operator. Indosat, Telkomsel and XL Axiata is the top three biggest operator in Indo-nesia. It is an important thing to know how they aplly service quality, and make a com-parative studies. The result of this research is very usefull to give a guidance for new comer.In this research of writer use propagated kuesioner to 166 responder, with sampling pur-posive as method intake of sampel. As for analysis performed within this first research is validity test and of realibilitas to test to elegibility of kuesioner, is later;then continued with classic assumption test to know do usage of regresi as a means of analyse in this re-search is compatible. Hereinafter researcher analyse regresi to data from third operator type. Last analysis which conducted by researcher is to test hypothesis to third operator.Result of analysis indicate that at operator of telkomsel, variable influencing satisfaction of consumer of its service is variable of reliability (reliability) of emphaty  (empathy). while at operator of indosat variable influencing satisfaction of consumer of its service is varia-ble of reiability (reliability) of tangible (physical evidence). other the things of with XL axi-ata, variable having an effect on to satisfaction of consumer of its service only just varia-ble of reliability. so that from this research also can be taken by conclusion that to opera-tor of GPRS, reliability (reliability) of service product is important matter to reach for satis-faction of client.